2006
DOI: 10.1111/j.1462-2920.2005.00955.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of microbial communities identified in different developmental stages of Ixodes scapularis ticks from Westchester and Dutchess Counties, New York

Abstract: Ixodes scapularis ticks play an important role in the transmission of a wide variety of pathogens between various mammalian species, including humans. Pathogens transmitted by ticks include Borrelia, Anaplasma and Babesia. Although ticks may harbour both pathogenic and non-pathogenic microflora, little is known about how the diversity of the microflora within ticks may influence the transmission of pathogens. To begin addressing this question, we examined the composition of bacterial communities present in Ixo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
95
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(100 citation statements)
references
References 55 publications
4
95
0
1
Order By: Relevance
“…There were two previous studies of I. scapularis larval and nymph microbiota that, like the current study, showed a high prevalence of Rickettsia (4,14). Neither study reported similarities with REIS, probably because the REIS sequences are not yet available in GenBank and can be searched for only via their unassembled reads.…”
Section: Discussionsupporting
confidence: 72%
“…There were two previous studies of I. scapularis larval and nymph microbiota that, like the current study, showed a high prevalence of Rickettsia (4,14). Neither study reported similarities with REIS, probably because the REIS sequences are not yet available in GenBank and can be searched for only via their unassembled reads.…”
Section: Discussionsupporting
confidence: 72%
“…Likewise, previous studies have not accounted for the contribution of the host blood meal source and the nutritional status of the fleas, which has been documented to influence bacterial communities in arthropods (Moreno et al, 2006). As a result of the high level of prevalence and stable vertical transmission of R. felis in some colonies of C. felis, we hypothesize that R. felis directly influences the prevalence of other species of bacteria within the flea.…”
Section: Introductionmentioning
confidence: 81%
“…The nutritional status of the arthropod in relation to bacterial composition has been examined for other blood feeding arthropods (Moreno et al, 2006). There was a correlation between life stage, feeding and prevalence of some species of bacteria (for example, Borrelia and Sphingobacteriaceae) in Ixodes scapularis ticks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diverse microbial communities were found in these vectors, and most microbial species were represented sparsely or occurred in only a few individual vectors. Some studies also indicated that the composition of these microbial communities often varies across time and space (Kirstein et al, 1997;Wielinga et al, 2006;van Overbeek et al, 2008;Jones et al, 2010) and that these variations are linked largely to the characteristics of the arthropod (for example, its species, life stage, diet and blood engorgement level; Pidiyar et al, 2004;Moreno et al, 2006;Heise et al, 2010;Jones et al, 2010;Hawlena et al, 2013). Nevertheless, because vector-borne microbes spend a part of their lives in the blood of the vertebrate host, it is important to consider also the internal environment of this host.…”
Section: Introductionmentioning
confidence: 99%